Generation of switchable domain wall and Cubic–Quintic nonlinear Schrödinger equation dark pulse - Tiu, Zian Cheak; Suthaskumar, M.; Zarei, A.; Tan, S.J.; Ahmad, Harith; Harun, Sulaiman Wadi (Elsevier, 2015)
A switchable domain-wall (DW) and Cubic-Quintic nonlinear Schrödinger equation (CQNLSE) dark soliton pulse generation are demonstrated in Erbium-doped fiber laser (EDFL) for the first time. The DW pulse train operates at 1575 nm with a fundamental repetition rate of 1.52 MHz and pulse width of 203 ns as the pump power is increased above the threshold pump power of 80 mW. The highest pulse energy of 2.24 nJ is obtained at the maximum pump power of 140 mW. CQNLSE pulse can also be realized from the same cavity by adjusting the polarization state but at a higher threshold pump power of 104 mW. The repetition rate and pulse width of the CQNLSE dark pulses are obtained at 1.52 MHz and 219 ns, respectively. The highest energy of 0.58 nJ is obtained for the CQNLSE pulse at pump power of 140 mW.